THE INFLUENCE OF PRODUCT QUALITY, INDIVIDUAL SALES AND RELATIONAL MARKETING ON DECISIONS CUSTOMER PURCHASES AT PT. PANCA NIAGA JAYA LESTARI - Edgina Tris Louis; Elgine Tris Louis; Jurisman Simanjorang; Sunday Ade Sitorus; SUNDAY ADE SITORUS (Mount Hope Economic Global Journal, 2024)
Panca Niaga Jaya Lestari is a company engaged in the sale of fast-moving products , offering various brands such as Kurnia, Hatari, Fox, and Indodes. Located in Mekar Baru Kisaran, the company faces challenges from increasingly tight competition, which causes a decline in customer purchases every year. Although this decline is not very significant, if it is allowed to continue, it can have a greater negative impact. In this study, the population used was 197 customers. By using the Slovin sampling technique at a 95% confidence level and a 5% margin of error, the number of samples determined was 132 customers. The results of the study indicate that Product Quality has a positive and significant influence on Purchasing Decisions, Personal Selling also has a positive and significant influence on Purchasing Decisions, and Relationship Marketing also has a positive and significant influence on Purchasing Decisions. Overall, Product Quality, Personal Selling, and Relationship Marketing simultaneously have a significant influence on Purchasing Decisions.